Becoming Clara Schumann: Performance Strategies and Aesthetics in the Culture of the Musical Canon - Stefaniak, Alexander -1983 (Bloomington Indiana University, 2021)
"Well before she married Robert Schumann, Clara Schumann was already an internationally renowned pianist, and she concertized extensively for several decades after her husband's death. Despite being tied professionally to Robert, Clara forged her own career and played an important role in forming what we now recognize as the culture of classical music. Becoming Clara Schumann guides readers through her entire career, including performance, composition, edits to her husband's music, and teaching. Alexander Stefaniak brings together the full run of Schumann's concert programs, detailed accounts of her performances and reception, and other previously unexplored primary source material to illuminate how she positioned herself within larger currents in concert life and musical aesthetics. He reveals that she was not only an accomplished strategist--having played roughly 1,300 concerts in her 61-year career across western and central Europe-but also played an integral role in shaping the reception of her husband's music. Revolutionary for the time, Schumann earned success and prestige by crafting her own playing style, selecting and composing her own concerts, and acting as her own manager. By highlighting Schumann's navigation of music's gendered boundaries, Becoming Clara Schumann details how she cultivated her public image in order to win over audiences and embody some of her field's most ambitious aspirations for musical performance"--
Introduction -- Schumann's early-career concert vehicles : transcendent interiority and the cutting edge of popular pianism -- The imagined revelation fo musical works -- The compositional agency of the revelatory interpreter -- Clara Schuman's 1840 compositions and her midcentury persona -- Navigating and shaping local concert scenes and canons : Clara Schumann's 1854-1856 tours -- Revelatory interpretation and the performance of memory -- Epilogue.
Includes bibliographical references and index.
Keywords: Schumann, Clara -- 1819-1896; Music history; Cuckoo; Biography; Piano; Female